EXPLORING THE ROLE OF PROJECT GOVERNANCE AND STAKEHOLDER MANAGEMENT IN PUBLIC SECTOR INFRASTRUCTURE PROJECTS - Ishak Ismail; Asadullah Khan; Muhammad Waris; Hasnah Haron; Bachtiar H. Simamora (Bina Nusantara University, 2019)
In developing countries, governance of public sector projects is becoming increasingly more complex due to the varying nature of stakeholders and their expectations from the government to address their interest. As a result, policymakers and sponsoring agencies are more focusing on stakeholder management to ensure smooth execution, high performance and achieving desired outcomes. This study has conducted a systematic appraisal of the relevant literature to explore the thematic discussions on the role of project governance and stakeholder management in public sector infrastructure projects of Pakistan. The analysis reveals that project governance and stakeholder management is not widely been discussed in the Pakistan specific studies. Therefore, this research proposes project governance and stakeholder management as key concerns of government decision-making strategies.